2023
DOI: 10.3390/ejihpe13090118
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Core Complex Training on Some Basketball-Related Aspects of Physical Strength and Shooting Performance

Ahmed K. Hassan,
Abdulmalek K. Bursais,
Mohammed S. Alibrahim
et al.

Abstract: Exercises for the core can be categorized as promoting core-stability, core-strength, or functionality, as these are crucial aspects of most sports activities. This study aimed to examine the effects of using core complex training (CCT), complex training (CT), and core exercise (CE) on some aspects of muscle strength and shooting performance in basketball players. The 36 participants were divided into three groups of 12 each, and then the experimental approach was applied to each group. The groups were labeled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…[ 8 10 ] Cumulatively, CT may have great potential in enhancing the competitive performance of modern pentathlon female athletes by simultaneously improving their strength and power, [ 11 ] .Furthermore, Hassan et al (2023) have demonstrated the efficacy of a Core Complex Training Program in boosting performance efficiency and muscular strength, thereby positively influencing match outcomes. [ 12 ] However, the specific effects of CT on enhancing the COD ability, as well as the strength and power of the lower limbs, in female basketball players have not been adequately examined.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 10 ] Cumulatively, CT may have great potential in enhancing the competitive performance of modern pentathlon female athletes by simultaneously improving their strength and power, [ 11 ] .Furthermore, Hassan et al (2023) have demonstrated the efficacy of a Core Complex Training Program in boosting performance efficiency and muscular strength, thereby positively influencing match outcomes. [ 12 ] However, the specific effects of CT on enhancing the COD ability, as well as the strength and power of the lower limbs, in female basketball players have not been adequately examined.…”
Section: Introductionmentioning
confidence: 99%
“…Jump to box training is designed to improve the strength, speed, and coordination of the muscles needed in jumping and shooting (Hassan et al, 2023;Andersson et al, 2019). This includes the leg muscles, core muscles, and arm muscles needed for the jump shoot (Nursantiko et al, 2022).…”
Section: Introductionmentioning
confidence: 99%